2019
DOI: 10.1021/jacs.9b08851
|View full text |Cite
|
Sign up to set email alerts
|

How To Maximize Birefringence and Nonlinearity of π-Conjugated Cyanurates

Abstract: Materials with large birefringence (Δn) are highly needed by fiber-optic isolators, whereas crystals showing strong second-order harmonic generation (SHG) are the key component for all-solid-state laser devices. Cyanurate constructed by the planar π-conjugated ring (C 3 N 3 O 3 , CY) is a class of fascinating materials exhibiting not only very large Δn (larger than that of calcite) but also strong SHG (2 times that of β-BaB 2 O 4 , BBO). Here, we report five new cyanurates (I−V) and their single-crystal struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
178
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(182 citation statements)
references
References 50 publications
3
178
1
Order By: Relevance
“…Generally, two types of oxide-based units with large macroscopic anisotropic mainly contribute to the birefringence: planar π-conjugated anions and second-order Jahn-Teller (SOJT) distorted cations. The former type is widely studied like metal cyanurates, borates and borate derivatives [14][15][16][17][18][19][20][21][22]. Cyanurates contain a considerable polarization unit with large birefringence and short absorption edge [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, two types of oxide-based units with large macroscopic anisotropic mainly contribute to the birefringence: planar π-conjugated anions and second-order Jahn-Teller (SOJT) distorted cations. The former type is widely studied like metal cyanurates, borates and borate derivatives [14][15][16][17][18][19][20][21][22]. Cyanurates contain a considerable polarization unit with large birefringence and short absorption edge [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[13] In particular, Sn 2 B 5 O 9 Cl [13] exhibits a remarkable enhancement of 16 times as compared with the isostructural Ba 2 B 5 O 9 Cl. It is of great importance and current interests to develop new strategies for birefringent materials.With a few exceptions, [14] to date birefringent materials are almost exclusively limited to oxides. In comparison, the possibility of peroxides as birefringent materials has long been overlooked, despite the fact that their localized conjugated p orbitals is highly polarizable.…”
mentioning
confidence: 99%
“…With a few exceptions, [14] to date birefringent materials are almost exclusively limited to oxides. In comparison, the possibility of peroxides as birefringent materials has long been overlooked, despite the fact that their localized conjugated p orbitals is highly polarizable.…”
mentioning
confidence: 99%
“…To the best of our knowledge, a plethora of alkali-and alkaline-earth metal cyanurates or cyanurate hydrates have been reported and characterized, [3][4][5][6][7][8][9][10][11] but the monoclinic compound Li 2 [HN 3 C 3 O 3 ]•2 H 2 O was the only one containing only Li + or Mg 2+ , respectively. Exploiting a review paper by Seifer, [12] we started to reproduce the reported synthesis for lithium and magnesium cyanurates in order to elucidate, if the diagonal relationship prevails under these conditions or if the general trend of "the higher the charge-to-radius quotient is, the more ARTICLE hydrated the cation becomes", will be confirmed.…”
Section: Introductionmentioning
confidence: 99%